THE FUZZY MODEL OF THE TECHNICAL SPECIALIST TRAINING PATH SELECTION - Dmitry P. Danilaev; Lilia Yu. Emaletdinova (Открытое образование (Москва))
The training path formation, deals with the employers rapidly changing requirements, is considered in this paper. The decision-making criteria of the appropriate training path selection are proposed. The fuzzy logic based mathematical model of decision support is considered.